2000
DOI: 10.1007/bf02350961
|View full text |Cite
|
Sign up to set email alerts
|

Injury-producing events among children in low-income communities: The role of community characteristics

Abstract: Study Purpose. Injury remains the leading cause of death in children aged 1 to 4 years.Past studies of determinants of injuries among young children have most often focused on the microlevel, examining characteristics of the child, parent, family, and home environments. We sought to determine whether and how selected neighborhood economic and physical characteristics within these low-income communities are related to differences in risk of events with injury-producing potential among infants and young children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(31 citation statements)
references
References 15 publications
1
29
0
1
Order By: Relevance
“…3,7,13,16 These variables include economic factors such as employment rate, income level, and education levels, as well as legislative factors such as highway speed limits, helmet laws, and firearm legislation. To contrast and compare the social, cultural, and legislative milieu of the two societies, information was obtained regarding these factors from state and provincial government databases.…”
Section: Methodsmentioning
confidence: 99%
“…3,7,13,16 These variables include economic factors such as employment rate, income level, and education levels, as well as legislative factors such as highway speed limits, helmet laws, and firearm legislation. To contrast and compare the social, cultural, and legislative milieu of the two societies, information was obtained regarding these factors from state and provincial government databases.…”
Section: Methodsmentioning
confidence: 99%
“…Schieber and Vegega (2002) suggested that the trend toward widening roadways to accommodate larger trucks may increase children's risk by making streets too difficult to cross during a light change and by eliminating sidewalks and refuge islands. O'Campo et al (2000) found that municipal housing violations, a proxy measure for housing conditions, significantly predicted events that were likely to produce an injury to a child.…”
Section: Review Of the Literaturementioning
confidence: 98%
“…The last decade has seen an increase in the number of studies that incorporate a neighborhood focus in studies of a range of issues including child behavior problems (Beyers, Bates, Pettit, & Dodge, 2003;Brody et al, 2003;Caughy, O'Campo, & Muntaner, 2003, 2004Chase-Lansdale & Gordon, 1996;Colder, Mott, Levy, & Flay, 2000;Dorsey & Forehand, 2003;Kupersmidt, Griesler, DeRosier, Patterson, & Davis, 1995;Simons, Johnson, Beaman, Conger, & Whitbeck, 1996;Simons et al, 2002;Xue, Leventhal, Brooks-Gunn, & Earls, 2005), child cognitive outcomes (Brooks-Gunn, Duncan, Klebanov, & Sealand, 1993;Caughy & Franzini, 2005;Chase-Lansdale & Gordon, 1996;Kohen, Brooks-Gunn, Leventhal, & Hertzmann, 2002), and child health outcomes such as low birth weight (O'Campo, Xue, Wang, & Caughy, 1997) and injury (O'Campo, Rao, Gielen, Royalty, & Wilson, 2000). There is a small body of literature examining neighborhood influences on academic achievement specifically, but most of this research has been with either adolescents (Bowen, Bowen, & Ware, 2002;Cook, Herman, Phillips, & Settersten, 2002;Ensminger, Lamkin, & Jacobson, 1996;Tama, Leventhal, & Brooks-Gunn, 2004) or older school-age children (Gutman & McLoyd, 2000;Schwartz & Gorman, 2003;Shumow, Vandell, & Posner, 1999).…”
mentioning
confidence: 99%